2004
DOI: 10.1074/jbc.m404376200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced G Protein-coupled Signaling Efficiency in Retinal Rod Outer Segments in Response to n-3 Fatty Acid Deficiency

Abstract: The fatty acid (FA) docosahexaenoic acid (DHA, 22: 6n-3) is highly enriched in membrane phospholipids of the central nervous system and retina. Loss of DHA because of n-3 FA deficiency leads to suboptimal function in learning, memory, olfactory-based discrimination, spatial learning, and visual acuity. G protein-coupled receptor (GPCR) signal transduction is a common signaling motif in these neuronal pathways. Here we investigated the effect of n-3 FA deficiency on GPCR signaling in retinal rod outer segment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
153
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 211 publications
(164 citation statements)
references
References 39 publications
6
153
0
5
Order By: Relevance
“…Docosahexaenoic acid (DHA, 22:6, n-3), a long-chain n-3 polyunsaturated fatty acid, is highly enriched in the nervous system (5). Inadequate supply of n-3 fatty acids during prenatal and postnatal development decreases the levels of DHA in neuronal tissues with a reciprocal increase of docosapentaenoic acid (DPA, 22:5 n-6) (6), leading to a variety of visual, cognitive, and͞or behavioral deficits in animal models (7)(8)(9). Conversely, dietary supply of DHA during infancy has been shown to improve mental development in humans (10,11).…”
mentioning
confidence: 99%
“…Docosahexaenoic acid (DHA, 22:6, n-3), a long-chain n-3 polyunsaturated fatty acid, is highly enriched in the nervous system (5). Inadequate supply of n-3 fatty acids during prenatal and postnatal development decreases the levels of DHA in neuronal tissues with a reciprocal increase of docosapentaenoic acid (DPA, 22:5 n-6) (6), leading to a variety of visual, cognitive, and͞or behavioral deficits in animal models (7)(8)(9). Conversely, dietary supply of DHA during infancy has been shown to improve mental development in humans (10,11).…”
mentioning
confidence: 99%
“…DHA comprises £ 80 % of the PUFA in the retina outer segment disks, and phospholipids are present in which both fatty acids are DHA. In vitro studies have provided evidence that DHA plays a role in photoreceptor signal transduction by influencing the ability of photons to transform rhodopsin to the activated meta-rhodopsin ll state and the efficiency of G-protein-coupled receptor signalling (Niu et al 2004). More recently, it has been shown (Soubias et al 2006) that there are specific binding sites for DHA in the rhodopsin molecules.…”
Section: Pufa In Human Milk and The Breast-fed Infantmentioning
confidence: 99%
“…Studies of mammalian retina revealed that DHA accounts for half of the total fatty acid content in the retina (Stinson et al 1991). The functional importance of DHA may be related to the interaction of the photoactive protein rhodopsin with DHAcontaining phospholipids (Gordon & Bazan, 1990;Niu et al 2004). Phospholipid bilayers rich in DHA have a high fluidity and enhanced rates of fusion and permeability which are characteristics vital to the normal functioning of photoreceptor cells (Giusto et al 2000).…”
Section: Infant Developmentmentioning
confidence: 99%